Konstruksi Skala Sikap terhadap Pelajaran Matematika dan Sains - Jelpa Periantalo; Fadzlul Fadzlul; Eka Saputra (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2014)
Student attitude toward subject is strong predictor for academic successful. Student with positive attitude shows good academic achievement and attitude poor achievement. Earlier information about student attitude can optimilize academic successful.  Education stake holders can change attitude. Therefore, it needs a measurement to know student attitude toward subject. The purpose of research is to construct scale attitude toward Mathematics and Natural Sciences subject. Instrument should be valid, reliable, and discriminative and practice. Research used psychological measurement method. It used 185 high school students for subject. It used semantif differential method in scale (1-7). There were 68 items in scale. Factorial validity confirmed three factor construct a scale. Convergent validity showed there was positive correlation among scale component. Scale had internal consistency reliability 0,84 and test parallel reliability 0,92. All items had discrimination power D  > 4,00. Final scale uses 12 items. Instruction and scoring can be done easily. Scale has good psychometric properties.  It has good validity, satisfied reliability, high discrimination power for items, and practice in used.